1986
DOI: 10.1161/01.res.58.1.157
|View full text |Cite
|
Sign up to set email alerts
|

The control of sugar uptake by metabolic demand in isolated adult rat heart cells.

Abstract: SUMMARY. To investigate the control of sugar uptake by metabolic demand, we used isolated quiescent adult rat heart cells in suspension, under conditions similar to those found during anoxia. Metabolic demand was varied by exposing cells to rotenone plus various levels of ptrifluoromethoxyphenylhydrazone. Without glucose, the time taken for half of the cells to undergo contracture was inversely proportional to the metabolic demand as measured by the rate of lactate production. For any metabolic demand, the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Alternatively, heterogeneity may be intercellular-the large outward conductance ofa few cells that are ATP depleted electrotonically shunting intact cells. This situation would be compatible with the large cell-tocell variability in lag duration that precedes contractile failure and with the heterogeneity in time of ATP depletion found in anaerobic cell suspensions (9). The latter studies showed that substantial ATP depletion precedes structural contracture by 1-6 min, similar to the time elapsing between contractile failure and contracture in our studies.…”
Section: Results An] Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Alternatively, heterogeneity may be intercellular-the large outward conductance ofa few cells that are ATP depleted electrotonically shunting intact cells. This situation would be compatible with the large cell-tocell variability in lag duration that precedes contractile failure and with the heterogeneity in time of ATP depletion found in anaerobic cell suspensions (9). The latter studies showed that substantial ATP depletion precedes structural contracture by 1-6 min, similar to the time elapsing between contractile failure and contracture in our studies.…”
Section: Results An] Discussionsupporting
confidence: 90%
“…The mechanism of contractile failure has been difficult to study in multicellular preparations because of the effects of heterogeneity (8)(9)(10) and decreased cell-to-cell electrical coupling during hypoxia (11). To produce hypoxia in a single isolated cell, however, a Po2 as low as 0.15 torr (1 torr = 133 Pa) must be achieved (12).…”
mentioning
confidence: 99%
“…Metabolic depletion rapidly stimulates sugar transport in these tissues (33)(34)(35). In this study, we demonstrate rapid depletion of ATP in bEnd.3 cells using metabolic poisons.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have used the metabolic poisons KCN and FCCP to induce acute metabolic stress in cardiomyocytes, skeletal muscle, and nucleated erythrocytes (33)(34)(35). Metabolic depletion rapidly stimulates sugar transport in these tissues (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The method is an extension of that previously used in our laboratory for measuring solute fluxes. [24][25][26] The new feature of the method is that concentrated cells are labeled with 22Na to a high specific activity and then diluted 10-fold into unlabeled medium before centrifugation. The dilution results in a 10-fold higher specific activity of 22Na inside the cell compared with 22Na outside and hence allows a 10-fold enhancement of the sensitivity of measurement of intracellular sodium compared with that of our basic method.…”
Section: Isotope Flux Measurementsmentioning
confidence: 99%